Defect prediction and experimental study on investment casting of K4169 superalloy complex thin-walled parts - WANG Xiang; ZHANG Ying; SUI Dashan; CHEN Zhongfeng; DONG Anping; GUO Zhao; QI Fei; YI Chushan; GUI Daxing (Cailiao gongcheng)
The filling and solidification processes in investment casting of typical K4169 nickel-based superalloy complex thin-walled casting are simulated by ProCAST finite element software.The temperature field during the casting process is analysed to predict the formation of defects. The complex thin-walled casting is produced by investment casting with the same process parameters， and its shrinkage level， microstructure， and tensile mechanical properties are studied.The results show that when the pouring temperature is 1530 ℃ and the preheating temperature of the mold shell is 1000 ℃， the filling of the molten metal is stable. The solidification conforms to the principle of sequential solidification. The overall defects of the casting are less； the micro-shrinkage average volume fraction of different parts is counted， and the highest is only 1.01%； the minimum secondary dendrite arm spacing（SDAS） in the thin-walled region is only 18.4 μm， and the maximum secondary dendrite spacing in the thick part is 38.8 μm； the as-cast microstructure of K4169 alloy is dendritic structure. After standard heat treatment， the dendrites grow and coarsen， and the dendritic morphology in the grains is not obvious. The average room temperature tensile strength of the standard heat-treated K4169 alloy is 785.0 MPa， the average yield strength is 659.7 MPa， and the average elongation is 13.9%. The difference in shrinkage porosity level significantly affects the tensile strength and yield strength， but the elongation change is not obvious.